In vitro antistaphylococcal effects of a novel 45S5 bioglass/agar-gelatin biocomposite films - Rivadeneira, Josefina (2013)
Aims: To assess the antibacterial efficacy of new composite materials developed from microparticles of 45S5 bioactive glass (BG) and agar-gelatin films. Methods and Results: In vitro antibacterial activity was evaluated against Staphylococcus spp. because of the importance of this pathogen in damaged tissues and in failures associated with biomaterial implants. To our knowledge, this is the first paper reporting on the suitable combination of BG and agar-gelatin for bioactive and antibacterial films. Bacterial suspensions up or below 105 CFU ml-1 reflecting situations of wound infection and of noninfection, respectively, were prepared and then put in contact with the biomaterials at 37°C. After 24 and 48 h of incubation, the pH value was measured and the staphylococci strains viability was determined by counting in Mueller-Hinton agar plates. Moreover, the biomaterials were prepared for observation under scanning electron microscopy (SEM). Biocomposites (BCs) showed a strong antibacterial effect against all staphylococci strains tested. Some differences were found depending on the strain, the inoculum size and the contact time. This effect was correlated with an alkalinization of the media. By SEM analyses, no bacterial presence was observed on the surface of BCs in any of the cell concentrations tested at any time. Conclusions: Overall, the coating of 45S5 BG on agar-gelatin films promoted BCs with strong antistaphylococcal activity. The effect was efficient under bacterial concentration up or below 105 CFU ml-1. Additionally, none of the strains were found on BCs surfaces. Significance and Impact of Study: 45S5 bioglass/agar-gelatin biocomposite films are reported for the first time. The results suggest a potential application as wound dressing.